Th17 regulating lower airway disease. Issue 1 (February 2016) - Cosmi, Lorenzo; Liotta, Francesco; Annunziato, Francesco
Abstract : Purpose of review: Th17 lymphocytes are now widely believed to be critical for the regulation of various chronic immune diseases, including asthma and chronic obstructive pulmonary disease. In this review, we discuss the current understanding of the role of Th17 cells in the pathogenesis of different asthma phenotypes and chronic obstructive pulmonary disease. Recent findings: It has been recently reported that Th17 cells and also a new population of Th17/Th2 cells accumulate in bronchoalveolar lavage fluid of asthmatic patients, and positively correlated with airway obstruction and steroid resistance. These patients often have steroid resistant severe asthma and a predominant bronchial neutrophilic inflammation. Summary: Steroid resistant severe asthma with predominant bronchial neutrophilic inflammation could benefit from IL-17 targeted therapies. In this view, the definition of clinical phenotypes and inflammatory endotypes of asthma in each patient will be necessary for personalizing the therapeutic approach.